History in the making: Voicing alternation as stop lenition via an automatic analysis of large-scale corpora in French and Spanish - Yaru Wu; Ioana Chitoran; Ioana Vasilescu; Martine Adda-Decker; Lori Lamel (Anuario del Seminario de Filología Vasca "Julio de Urquijo")
This study focuses on voicing alternation in French and Spanish stops, i.e. canonically voiceless /ptk/ realized as voiced [bdg] or canonically voiced /bdg/ realized as voiceless [ptk]. Forced alignment with voicing variants was used to annotate large speech corpora in French and in Spanish. The following factors of variation were examined: position in the word, preceding and following context, duration of the stop and that of surrounding phones, speech rate, part of speech, and the weight of these factors on voicing alternation. The voicing nature of the stops (whether the stop is phonologically voiceless /ptk/ or voiced /bdg/) turns out to be the factor that contributes the most to the prediction of voicing alternations among all investigated factors for Spanish, according to the random forest model. Whereas for French, the same factor comes after contextual and acoustic factors in the ranking. These results suggest that stop voicing patterns differently in these two Romance languages, although they both have a similar voiced-voiceless phonological contrast.